2013
DOI: 10.6007/ijarbss/v3-i9/215
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effectiveness of Reward Management System on Employee Performance through the Mediating Role of Employee Motivation Case Study: Isfahan Regional Electric Company

Abstract: Purpose: Analyzing the effectiveness of reward management system on employee performance through the mediating role of employee motivation was the purpose of the present survey. Method and tools: Given that staff department of Isfahan Regional Electric Company was the statistical population under study simple random sampling was used in this survey. Sample size was determined by means of Cochran formula (140 persons). Historical study and field study methods were the most important methods of data collection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 7 publications
0
8
0
10
Order By: Relevance
“…Social cognitive theory claims that rewards given for the success of challenging performance standards may result in high motivation (Schunk, 1989;Netz and Raviv, 2004). Karami et al (2013) determined the impact that a reward management system has on employee performance with the mechanism of the mediating role of employee motivation at Isfahan electric company. The results of their study revealed that reward management has a significant positive impact on the performance of the employee, and the motivation of the employee significantly mediated the effect of reward management system on employee performance.…”
Section: Intrinsic Rewards and Employee Motivationmentioning
confidence: 99%
“…Social cognitive theory claims that rewards given for the success of challenging performance standards may result in high motivation (Schunk, 1989;Netz and Raviv, 2004). Karami et al (2013) determined the impact that a reward management system has on employee performance with the mechanism of the mediating role of employee motivation at Isfahan electric company. The results of their study revealed that reward management has a significant positive impact on the performance of the employee, and the motivation of the employee significantly mediated the effect of reward management system on employee performance.…”
Section: Intrinsic Rewards and Employee Motivationmentioning
confidence: 99%
“…They intimate that substantial amount of research attest to the positive effect of leaders' rewards and punishment behaviors to employee performance. Karami et al (2013) found that rewards have positive and significant effects on employee performance. The findings reported by Podsakoff et al (2006) suggest that rewards and punishment behaviors are crucial for encouraging employee performance outcomes that are desired by leaders.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Compensation or reward management aims at the formulation and implementation of strategies and policies that are aimed at rewarding people fairly, equitably and consistently in accordance with their value to the organisation (Brauns, 2013;Karami, Dolatabadi & Rajaeepour, 2013;Pingle, 2014). It deals with the design, implementation and maintenance of reward practices that are geared towards the improvement of organisational, team, and individual performance (Dauda, 2010;Abolade, 2012).…”
Section: Compensation Managementmentioning
confidence: 99%